Marx and Engels’ Educational Thought and Its Innovation and Practice in the New Era - Lin, Feng (International Journal of Social Sciences and Public Administration, 2024)
The educational ideas deeply explored by Marx and Engels in revolutionary practice have strong vitality and important guiding significance. In the context of the new era, socialism with Chinese characteristics further enriches the educational ideas of Marx and Engels, emphasizes the cultivation of morality and clarifies the purpose of education; At the same time, traditional cultural education has been highlighted, and the role of education in cultural inheritance and spiritual construction has been played; The distribution of educational resources has been balanced, and educational equity has been improved; Education reform is also constantly deepening to cultivate innovative talents with innovative abilities. Therefore, we must always prioritize education as a strategic development priority; Deepen the reform of the education system and mechanism to promote the healthy development of education; Strengthening the construction of the teaching staff to safeguard the improvement of educational quality; Emphasize the joint efforts of the Party, government, society, schools, families, and individuals in education.